L-carnitine in experimental retinal ischemia-reperfusion injury - Alagoz, G; Celiker, U; Ilhan, N; Yekeler, H; Demir, T; Celiker, H (Karger, 2002)
The effect of L-carnitine on retinal ischemia-reperfusion injury was evaluated in guinea pigs. 90 min of pressure-induced retinal ischemia followed by 24 h of reperfusion was established in both eyes of 2 groups of animals receiving either L-carnitine (100 mg/kg repeated in 5 doses) or saline intraperitoneally. After enucleation of all the eyes, including those of a control group, malonyldialdehyde (MDA) levels and the thickness of the retinal tissue were measured in 3 groups. The mean MDA value and the tissue thickness of the L-carnitine-treated group were statistically insignificant versus the control group (p > 0.05 and p > 0.05, respectively). However, these values were significantly different in the group receiving saline versus the control group and that receiving L-carnitine (p < 0.001, p < 0.001 and p < 0.001, p < 0.001 respectively). L-Carnitine might be an alternative drug for ischemia-reperfusion injury of the retina. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: L-carnitine; ischemia-reperfusion injury; retina; guinea pig